Productivity of a portable winch system used in salvage logging of storm-damaged timber - Bilici, Ebru; Andiç, Güryay Volkan; Akay, Abdullah Emin; Sessions, John (2019)
Storm damages result in serious losses in many regions, primarily by stem breakage or blowdown. Extraction of storm-damaged trees often requires more difficult than normal skidding activities due to obstacles created during the storm. In this study, the productivity of a portable winch was evaluated as a possible alternative to recover storm-damaged timber. Field measurements were conducted in the Alabarda Forest Enterprise Chief located near the city of Kütahya in western Turkey, where storm damage often occurs during the winter season. The time study was implemented in two slope classes (35% and 55%) and two skidding distances (40 m and 60 m). All timber was skidded uphill. A regression mode was developed that related productivity to log volume, ground slope and skidding distance. The highest percentage of total cycle time was observed for skidding logs to the landing. The highest productivity (3.96 m3/hour) was found at the shorter skidding distance (40 m) and the lower ground slope (35%). Statistical analyses indicated that productivity was most highly affected by log volume, followed by skidding distance and ground slope. Larger log loads increased productivity, while both longer skidding distances and steeper slopes reduced productivity.
Bibliografija: str. 317-318.
Abstract.
Keywords: Štete od oluje -- Izvlačenje drva -- Vitlo -- Prijenosno vitlo -- Učinkovitost